2001
DOI: 10.1136/adc.84.6.508
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow transplantation for CD40 ligand deficiency: a single centre experience

Abstract: (Arch Dis Child 2001;84:508-511)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
38
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 21 publications
1
38
0
Order By: Relevance
“…As for pre-transplantation infections in our series, only one patient had cryptosporidial infection and five out of seven patients had previous episodes of P. carinii pneumonitis. As mentioned in previous reports, cryptosporidial infection seemed to correlate with a poor outcome, but P. carinii infection did not [20]. Although both two patients with poor outcome had P. carinii pneumonitis previously, P. carinii infection itself was well managed after transplantation.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…As for pre-transplantation infections in our series, only one patient had cryptosporidial infection and five out of seven patients had previous episodes of P. carinii pneumonitis. As mentioned in previous reports, cryptosporidial infection seemed to correlate with a poor outcome, but P. carinii infection did not [20]. Although both two patients with poor outcome had P. carinii pneumonitis previously, P. carinii infection itself was well managed after transplantation.…”
Section: Discussionsupporting
confidence: 60%
“…Nonmyeloablative conditioning regimens consisted of fludarabine and melphalan with or without ATG or anti-lymphocyte globulin and were used in four cases with high-risk features, such as severe pretransplant liver complications or sclerosing cholangitis. Although these preliminary reports are relatively successful, Khawaja et al reported four failures out of eight transplanted patients, and that risk and death were associated with older age, pre-transplant liver damage, and cryptosporidial infection [20].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…8 However, the presence of C. parvum infection, especially when complicated by sclerosing cholangitis, impairs the results of BMT. Khawaja et al 9 reported three cases where patients suffering from severe C. parvum infection died soon after BMT. 9 In this report, we describe two brothers with HIGM1 who were both suffering from severe C. parvum infection with gastroenteritis and sclerosing cholangitis.…”
Section: Discussionmentioning
confidence: 99%
“…Khawaja et al 9 reported three cases where patients suffering from severe C. parvum infection died soon after BMT. 9 In this report, we describe two brothers with HIGM1 who were both suffering from severe C. parvum infection with gastroenteritis and sclerosing cholangitis. They underwent successful BMT from a genoidentical HLA sibling and recovered from the C. parvum infection.…”
Section: Discussionmentioning
confidence: 99%